A genome-wide approach for identification and characterisation of metabolite-inducible systems - Erik K. R. Hanko (Nature Portfolio, 2020)
Inducible gene expression tools have important applications as genetically encoded biosensors. Here the authors conduct a genome-wide approach to identify and utilise functional sensors.